SHORT STRUCTURED SUMMARY USING 5W1H TO IMPROVE 10TH GRADE STUDENT'S WRITING COMPETENCE - ALAM, BINTANG PERMATA (RETAIN, 2021)
Short Structured Summary is one of the learning strategies which aims to assist students in improving their writing competence. In addition, the use of this strategy indirectly helps students in understanding the text. In implementing this strategy, classes were conducted virtually with three intensity meetings. The material taught to students was narrative text material. After the Short Structured Summary using the 5W1H approach was implemented, the researcher then analyzed the students' writing skills through the assignments given by the teacher and the results of interviews with five student representatives. This research was designed as qualitative descriptive research in which data was obtained through the observation process. Field notes were also carried out to collect all information related to teachers' and students' teaching and learning processes. Based on field notes, the teacher has gone through the teaching stages well, from opening to closing in each meeting. Through virtual meetings, the teacher approached students by introducing narrative text first, then explained and implemented the Short Structured Summary strategy using 5W1H at the next meeting. The results of this strategy's implementation, students were assigned to write a short structured summary to be assessed using an assessment rubric that the researcher has set. Semi-structured interviews were also conducted with five student representatives to complement the data obtained. This study found that the teacher has implemented the Short Structured Summary using the 5W1H strategy to improve students' writing competence.